Affixes Forming Nouns, Verbs, Adjectives and Adverbs in the Kaili Languange, Rai Dialect - Gusti Ayu Gita Masari; Diah Havidotul Imaniah; Maudy Rahmiati; Sartiwi Sartiwi (Civiliza Publishing, Indonesia., 2026)
This study examines the affixes that form nouns, verbs, adjectives and adverbs in the Kaili language of the Rai dialect, aiming to understand the process of word formation through the combination or addition of affixes in the Kaili language of the Rai dialect. The Kaili language of the Rai dialect is one of the Kaili language families spoken by the people of Central Sulawesi, especially the city of Palu, Donggala Regency, Sigi Regency and its surroundings. The methods used in this study are the distributional method, the Direct Element Sharing (BUL) technique, the Lesap technique, the Change technique, and the Expand technique. The data source of this study is the oral speech of native speakers of the Kaili language of the Rai dialect in Sipeso Village, Sindue Tobata District, Donggala Regency, Central Sulawesi Province. The results of the study indicate that the Kaili Rai Dialect has a productive affix formation process, including Prefixes (initial) mom-, no-, na-, mo-, ri, po-, topoN-, Suffixes (final) -sa, -i, -na, -mo, -ka, Infixes (insertions) -um-, -in-, Confixes (initial-final) ni-/-ka, ka-/-na, na-/-mo, pan-/-a. Each affix has a different grammatical function and meaning in the formation of word classes. The results of this study provide an important contribution in the documentation and description of regional languages that are increasingly threatened with extinction for the younger generation.